PERLUASAN WEWENANG MAHKAMAH KONSTITUSI SEBAGAI PENGAWAL KONSTITUSI - Yenny, Oktavani (TANJUNGPURA LAW JOURNAL, 2020)
Becoming one of the materials inside the fifth amendment of Undang-Undang Dasar Negara Republik Indonesia 1945 (The 1945 Constitution of Republic Indonesia), Constitutional Court authority now has become one of the essential concerns given that the function as "the guardian of the constitution" it became crucial in the protection of the constitutional rights of citizens. Along with times, violations of citizens constitutional rights are no longer based solely on legal norms, but violations committed against the application of norms by state institutions or public bureaucratic institutions (Constitutional Complaint). In addition, the need for institutions that deal with constitutional questions over the existence of a legal norms whose constitutionality is doubtful (Constitutional Question) as well as the authority of the Judicial Review carried out by institutions holding judicial power, called the Supreme Court and the Constitutional Court, led to a dualism of Judicial Review which turned out to be vulnerable to presenting legal issues. The methodology used in this study is normative juridical with a qualitative approach and using literatures. From the results of this study it was concluded that the need for additional of Constitutional Complaint and Constitutional Question authority as the authority of the Constitutional Court as well as a one-stop Judicial Review system in the Constitutional Court became very important carrying out its function as a guardian of the Constitution.Menjadi salah satu materi dalam Amandemen kelima Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, kewenangan Mahkamah Konstitusi kini menjadi salah satu perhatian penting karena mengingat fungsinya sebagai the guardian of the constitusion menjadi krusial dalam perlindungan terhadap hak-hak konstitusional warga negara. Seiring dengan perkembangan zaman, pelanggaran hak-hak konstitusional warga negara tidak lagi hanya berdasarkan pada norma hukum, namun pelanggaran yang dilakukan atas penerapan suatu norma oleh lembaga negara atau lembaga birokrasi publik (Constitutional Complaint). Selain itu, perlunya lembaga yang menangani pertanyaan-pertanyaan konstitusional atas keberadaan suatu norma hukum yang diragukan konstitusionalitasnya (Constitutional Question) serta kewenangan Judicial Review yang dijalankan oleh lembaga pemegang kekuasaan kehakiman, yaitu Mahkamah Agung dan Mahkamah Konstitusi menimbulkan dualisme Judicial Review yang ternyata rentan menghadirkan persoalan hukum. Metodologi yang digunakan dalam penelitian ini berupa yuridis normatif dengan pendekatan kualitatif dan menggunakan bahan kepustakaan. Dari hasil penelitian ini disimpulkan bahwa perlunya penambahan kewenangan Constitutional Complaint dan Constitutional Question sebagai kewenangan Mahkamah Konstitusi serta sistem satu atap Judicial Review di Mahkamah Konstitusi menjadi sangat penting sebagai bentuk pelaksanaan fungsinya sebagai pengawal Konstitusi.